The effect of gamification on motivation in the education of pre-service social studies teachers - Yildiz, İsmail; Topçu, Ersin; Kaymakci, Selahattin (Elsevier BV, 2021)
Abstract The purpose of this study was to examine the effect of gamification on motivation levels of pre-service teachers in social studies teaching. As a quantitative research method, semi-experimental design with pretest-posttest and control group was used in the study. The research was carried out with 2nd year undergraduate students in the Department of Social Studies Education in the spring semester of the 2018-2019 academic year in Turkey. Participants consisted of 56 teacher candidates, 36 in experimental group and 20 in control group. Motivation scale and structured interview form were implemented as data collection tools. According to the findings obtained after the four-week application period, the motivation of the experimental group teacher candidates for the course increased significantly compared to those of the control group. As a natural consequence of the increase in motivation - the most basic component of creativity, it was assumed that the creative skills of the participants increased too. On the other hand, the qualitative results indicated that they held positive opinions about the lessons i.e., the lessons became more fun. Moreover, the participants stated that gamification added a fun competition to the lesson, and they intended to use it in their own lessons in the future.
Keywords: 4. Education; 16. Peace & justice; 3. Good health